Tipologi Fasad Bangunan Pada Rumah Besak di Kampung Arab Assegaf Palembang - Cahyani, Regita Dwi; Putra, Evan Syah; Asysyauki, Akmad Hamdi; Sary, Reny Kartika (Jurnal TekstuReka, 2023)
Assegaf Village is a settlement located on the banks of the Musi River and is inhabited by residents of Arab descent. This region continues to uphold traditional and cultural norms which are closely related to religious values. With the development it has experienced, Assegaf Village has given birth to a new settlement which still maintains its special characteristics as a place to live for people of Arab descent. This village has high historical and cultural value. The research methods used include field surveys, visual documentation, and interviews with nearby workers to understand the unique characteristics of the building facade. The aim of this research is to analyze and classify the typology of building facades in besak houses in Kampung Arab Assegaf Palembang. The findings of this research are that this building was built in the 19th century using the Indies House type. The typology of the Rumah Besak building facade is more of a modern architectural style as seen in the composition of the facade which is not symmetrical but does not forget the elements of traditional Palembang houses